Biosorption of zinc (II) from synthetic wastewater by using Inula Viscosa leaves as a low-cost biosorbent: Experimental and molecular modeling studies. (15th January 2023) - Rouibah, Karima; Ferkous, Hana; Delimi, Amel; Himeur, Touhida; Benamira, Messaoud; Zighed, Mohammed; Darwish, Ahmad S.; Lemaoui, Tarek; Yadav, Krishna Kumar; Bhutto, Javed Khan; Ahmad, Akil; Chaiprapat, Sumate; et al.
Abstract: The use of biosorption as a strategy for lowering the amount of pollution caused by heavy metals is particularly encouraging. In this investigation, a low-cost and efficient biosorbent, Inula Viscosa leaves were used to remove zinc ions (Zn 2+ ) from synthetic wastewater. A Fourier transform infrared spectroscopy experiment, a scanning electron microscopy experiment, and an energy dispersive X-ray spectroscopy experiment were used to describe the support. Several different physicochemical factors, such as the beginning pH value, contact duration, initial zinc concentration, biosorbent dose, and temperature, were investigated in this study. When the Langmuir, Freundlich, Temkin, Toth, and Redlich-Peterson models were used to match the data from the Inula Viscosa leaves biosorption isotherms, it was found that the biosorption isotherms correspond most closely with the Langmuir isotherm. On the other hand, the kinetic biosorption process was investigated using pseudo-first-order, pseudo-second-order (PS2), and Elovich models. The PS2 model was the one that provided the most accurate description of the biosorption kinetics. The thermodynamics process shows the spontaneous and endothermic character of Zn 2+ sorption on Inula Viscosa leaves, which also entails the participation of physical interactions. In addition, the atom-in-molecule analysis, density functional theory, and the conductor like screening model for real solvents, were used to investigate the relationship that exists between quantum calculations and experimental outcomes. Graphical abstract: Image 1 Highlights: Inula Viscosa was used as an effective biosorbent for Zn (II). FTIR, SEM, and EDX fully revealed the biosorption mechanism. The concentration of metal, contact time, and pH affect zinc (II) biosorption. The interaction between significant molecules and zinc (II) was investigated by molecular modeling. The experimental results are in good agreement with the theoretical investigation.